1997
DOI: 10.1515/reveh.1997.12.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Vibrios in the Natural Aquatic Environment

Abstract: In recent years, members belonging to the genus Vibrio of the family Vibrionaceae have acquired increasing importance because of the association of several of its members with human disease. The most feared of the Vibrio species is Vibrio cholerae, the causative agent of cholera, a devastating disease of global significance. Other important vibrios of medical importance are V. parahemolyticus, V. vulnificus, V. mimicus, and to a lesser extent V. fluvialis, V. furnissii, V. hollisae, and V. damsela. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 145 publications
2
84
0
3
Order By: Relevance
“…It has been demonstrated that vibrio species are pathogenic for humans, causing intestinal and extra-intestinal infections (21)(22)(23). Therefore, their detection as environmental contaminants is of a paramount importance for the control of both water quality and disease transmission (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that vibrio species are pathogenic for humans, causing intestinal and extra-intestinal infections (21)(22)(23). Therefore, their detection as environmental contaminants is of a paramount importance for the control of both water quality and disease transmission (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…At least 12 species of the Vibrio genus are potentially pathogenic to humans [1]. Particularly Vibrio parahaemolyticus and Vibrio vulnificus, but also Vibrio alginolyticus and Vibrio cholerae are known as causative agents of seawater-related illnesses, such as seafood poisoning in association with gastrointestinal infections [2][3][4] and infections of wounds and mucous membranes [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In cholera-endemic areas of developing countries where clean drinking water is not easily available, large numbers of people use environmental water sources Chakraborty et al, 1997;Nair et al, 2010 . It has, thus, been suggested that cholera can continue to spread because such water is contaminated by V. cholerae.…”
Section: Vibrio Choleraementioning
confidence: 99%